Atypical HNPCC owing to MSH6 germline mutations: analysis of a large Dutch pedigree. Issue 5 (1st May 2001) - Wagner, A; Hendriks, Y; Meijers-Heijboer, E J; de Leeuw, W J F; Morreau, H; Hofstra, R; Tops, C; Bik, E; Bröcker-Vriends, A H J T; van der Meer, C; Lindhout, D; Vasen, H F A; et al.
Abstract : Hereditary non-polyposis colorectal cancer (HNPCC) is the most common genetic susceptibility syndrome for colorectal cancer. HNPCC is most frequently caused by germline mutations in the DNA mismatch repair (MMR) genes MSH2 and MLH1 . Recently, mutations in another MMR gene, MSH6 (also known as GTBP ), have also been shown to result in HNPCC. Preliminary data indicate that the phenotype related to MSH6 mutations may differ from the classical HNPCC caused by defects in MSH2 and MLH1 .  Here, we describe an extended Dutch HNPCC family not fulfilling the Amsterdam criteria II and resulting from a MSH6 mutation. Overall, the penetrance of colorectal cancer appears to be significantly decreased (p<0.001) among the MSH6 mutation carriers in this family when compared with MSH2 and MLH1 carriers (32% by the age of 80 v >80%).  Endometrial cancer is a frequent manifestation among female carriers (six out of 13 malignant tumours). Transitional cell carcinoma of the urinary tract is also relatively common in both male and female carriers (10% of the carriers).  Moreover, the mean age of onset of both colorectal cancer ( MSH6 v MSH2/MLH1 = 55 years v 44/41 years) and endometrial carcinomas ( MSH6 v MSH2/MLH1 = 55 years v 49/48 years) is delayed. As previously reported, we confirm that the pattern of microsatellite instability, in combination with immunohistochemical analysis, can predict the presence of a MSH6 germline defect.  The detailed characterisation of the clinical phenotype of this kindred contributes to the establishment of genotype-phenotype correlations in HNPCC owing to mutations in specific mismatch repair genes.